Effects of huperzine A on electroencephalography power spectrum in rabbits - Guan Lin-chu; Chen Shuang-shuang; Lu Wei-hua; Tang Xi-can (Acta Pharmacologica Sinica; Vol 10, No 6 (November 1989): Acta Pharmacologica Sinica, 2016)
Huperzine A (Hup-A) is a new alkaloid extracted from Huperzia serata in China. The effects of Hup-A on learning and memory are superior to those of physostigmine (Phys). The purpose of this paper is to observe the effects of Hup-A on EEG and EEG power spectrum in rabbits with micro-computer analysis. Hup-A 0.1 mg/kg iv in conscious rabbits produced, after 0.5 min, an alert EEG pattern, which showed decreases of lower frequency components and the total EEG power in cortical area, and the dominant frequency transferred from delta rhythm to theta rhythm in hippocampus. The same effects were seen with Phys 0.1 mg/kg. Scopolamine (Scop, 0.2 mg/kg iv) reversed significantly these effects of Hup-A (10 micrograms/rabbit, icv), but Scop butylbromide (0.4 mg/kg, iv) which can not pass the blood-brain barrier did not. Hup-A 0.2 mg/kg iv or Phys 0.3 mg/kg iv antagonized the EEG effects of Scop 0.3 mg/kg iv. The results indicate that the effects of Hup-A are closely related to the action on the central cholinergic system.